Manufacturing system design based on axiomatic design: Case of assembly line - Triki Hager; Hachicha Wafik; Masmoudi Faouzi (Journal of Industrial Engineering and Management (JIEM), 2017)
Purpose: In this paper, a combined Production Line Design (PLD) process which includes many design aspects is presented, developped and validated. Design/methodology/approach: The PLD process is based on the SADT (Structured Analysis and Design Technique) diagram and the Axiomatic Design (AD) method. Practical implications: For a purpose of validation, this proposed process has been applied in a manufacturing company and it has been validated by simulation. Findings: The results of the validation indicated that the production line designed by this process is outperformed the initial line of the company. Originality/value: Recently, the problems of production line design (PLD) have attracted the attention of many researchers. However, only a few studies have treated the PLD which includes all design aspects. In this work, a combined PLD porcess is presented. It should be noted that the proposed process is simple and effective.
Keywords: 650; production line design; assembly line; axiomatic design; SADT; configuration; performance